Detailed Study on Age Related Pattern of Awareness and Basic Knowledge on Zika Virus Disease among Women Visiting Children Immunization Unit in Enugu State University Teaching Hospital, Southeast Nigeria - Edmund O. Ndibuagu; Innocent I. Okafor; Sussan U. Arinze-Onyia (Challenges in Disease and Health Research Vol. 5, 2021)
Background: Zika virus is an infective agent of significant Public Health importance, which re-emerged in 2015. It is transmitted through mosquito bite, and associated with microcephaly and some other neurological malformations in some babies of infected mothers. Mild infections with this virus were recorded in Americas, Asia, Africa, and the Pacific region in the past; but it was in 2015 that it re-emerged in Brazil as a disease of real Public Health importance. WHO declared Zika virus infection a "Public Health Emergency of International Concern" on February 1, 2016, but lifted the emergency declaration in November of the same year. Objectives: The objective of this study was to assess the age-related pattern of the awareness and basic knowledge of Zika virus infection among women who bring children for immunization, in a teaching hospital, southeast Nigeria. Materials and Methods: The study was conducted in the Immunization unit of a Teaching Hospital, Southeast Nigeria, between November 2016 and February 2017. It was a quantitative, observational, descriptive, cross-sectional study, involving randomly selected 256 women who brought children for immunization. Pre-tested, interviewer-administered, structured questionnaire was used; and data was analyzed using SPSS version 20.0 for windows. Results: Highest number of respondents [112 (43.8%)] were from 30 to 39 age group, followed by those aged 20 to 29 years [108(42.2%)]. Up to 38.3% of respondents had never heard about Zika virus, though this was not statistically significant when compared to the 61.7% that were aware of Zika Virus Disease (P = 0.92). Highest number heard it through television [57(36.1%)]. Overall, respondents that were 20 to 29 years of age recorded mean percentage basic knowledge score of 54.6%, while those in the 30 to 39 years age range recorded 49.8%. Conclusions: Many respondents either had never heard about Zika virus, and also many exhibited poor basic knowledge on Zika virus disease. Among respondents within the child bearing age group, only those within the age range of 20 to 29 recorded mean percentage basic knowledge score that was over 50.0% (54.6%). It is therefore important to develop good strategies aimed at addressing these awareness and knowledge gaps among women of child-bearing age, who are mostly affected by Zika virus disease.